Long term in vivo observation of maize leaf xylem embolism, transpiration, and photosynthesis during drought and recovery - Allen, Brendan S., author; Ocheltree, Troy W., advisor; Gleason, Sean M., advisor; Knapp, Alan K., committee member (Colorado State University. Libraries, 2024)
Plant water transport is essential to maintain turgor, photosynthesis, and growth. Water is transported in a metastable state under large negative pressures, which can result in embolism, i.e., the loss of function by the replacement of liquid xylem sap with gas, as a consequence of water stress. Unfortunately, the detection of embolism is difficult because any manipulation of the xylem to facilitate measurement (e.g., cutting) can unintentionally introduce embolism. Therefore, our understanding of the timing of embolism, relative to other physiological responses, is incomplete. To avoid experimental artifacts, we used non-invasive methods to quantify embolism occurrence in maize leaves to characterize the sequence of physiological responses (leaf shrinkage, photosynthesis, chlorophyll fluorescence, and transpiration) during severe water stress. Embolism formation occurred after other physiological processes decreased and was irreversible upon rewatering. Recovery of transpiration, net CO2 assimilation, and photosystem II efficiency were aligned with the severity of embolism, whereas these traits returned to near pre-stress levels in the absence of embolism. A better understanding of the relationships between embolism occurrence and downstream physiological processes during stress and recovery is critical for the improvement of crop productivity and resilience.